2016
DOI: 10.1021/acs.joc.6b00657
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)-Catalyzed Enantioselective Synthesis of α-(Trifluoromethyl)arylmethylamines

Abstract: We describe a method for the synthesis of α-(trifluoromethyl)arylmethylamines that consists of the palladium(II)-catalyzed addition of arylboroxines to imines derived from trifluoroacetaldehyde. Palladium acetate is used as a catalyst with electron-neutral or electron-rich arylboroxines, and it was found that addition of an ammonium or silver salt was crucial to promote the reaction of electron-poor boroxines. With (S)-t-Bu-PyOX as the chiral ligand, this method delivers a variety of α-trifluoromethylated amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Lautens and co-workers later reported a modified catalytic system to address some of the synthetic challenges they had encountered (Scheme 6, bottom). 36 Switching to Cl 2 Pd-(PyOX) complex 8 with a silver additive that renders the Pd(II) species cationic facilitates transmetalation of the arylboroxine. Similar cationic Pd(II) catalysts have been utilized by the Stoltz group 37 for conjugate addition with arylboron nucleophiles and by Hayashi and co-workers 38 for addition to cyclic sulfonyl imines.…”
Section: Addition Of Carbon-and Heteroatom-based Nucleophiles To Trif...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lautens and co-workers later reported a modified catalytic system to address some of the synthetic challenges they had encountered (Scheme 6, bottom). 36 Switching to Cl 2 Pd-(PyOX) complex 8 with a silver additive that renders the Pd(II) species cationic facilitates transmetalation of the arylboroxine. Similar cationic Pd(II) catalysts have been utilized by the Stoltz group 37 for conjugate addition with arylboron nucleophiles and by Hayashi and co-workers 38 for addition to cyclic sulfonyl imines.…”
Section: Addition Of Carbon-and Heteroatom-based Nucleophiles To Trif...mentioning
confidence: 99%
“…Lautens and co-workers later reported a modified catalytic system to address some of the synthetic challenges they had encountered (Scheme , bottom) . Switching to Cl 2 Pd­(PyOX) complex 8 with a silver additive that renders the Pd­(II) species cationic facilitates transmetalation of the arylboroxine.…”
Section: Addition Of Carbon- and Heteroatom-based Nucleophiles To Tri...mentioning
confidence: 99%
“…[49] As direct precursors of imines and iminium ions, N,O-aminals were converted through asymmetric organocatalysis or metal catalysis to diverse enantiomerically enriched compounds including Nheterocycles. [50] For example, it has been observed that N,O-aminals have been involved in asymmetric Mannich reactions, [51][52][53][54][55] asymmetric nucleophilic alkylations, [56][57][58] asymmetric aza-Petasis-Ferrier rearrangement, [59] asymmetric Suzuki-Miyaura crosscoupling reactions, [60,61] asymmetric aza-Friedel-Crafts reactions, [62][63][64] asymmetric aza-Morita-Baylis-Hillman reactions [65,66] etc.…”
Section: Intermolecular Reactions With O-nucleophilesmentioning
confidence: 99%
“…On the other hand, the aldol reaction using trifluoroacetaldehyde (CF 3 CHO) have been widely developed for the synthesis of various secondary α‐trifluoromethylated alcohols and amines as precursors for antidepressants inhibitors of β‐Amyloid self assembly, calcimimetic drug, and liquid crystals . However, since CF 3 CHO is gaseous and unstable aldehydes, it can not be stored and normally exists as a hydrate or hemiacetal form due to the strong electron‐withdrawing property of the trifluoromethyl group.…”
Section: Introductionmentioning
confidence: 99%